The historiography of Alexander the Great - Classica et orientalia 2014 Breslau; Nawotka, Krzysztof 1960-; Rollinger, Robert 1964-; Wiesehöfer, Josef 1951-; Wojciechowska, Agnieszka (Wiesbaden Harrassowitz Verlag, 2018)
Historiography of Alexander the Great : an introduction / Krzysztof Nawotka, Josef Wiesehöfer and Agnieszka Wojciechowska -- Alexandre à Troie : images, mythe et realia / Pierre Briant -- Of philosophers and kings : concerning Philip II of Macedon's alleged "debt" to Plato / Kenneth R. Moore -- Patron the Phocian : a written "mercenary source"/ Nicolas Sekunda -- On the traces of Onesicritus. Some historiographical aspects of Alexander's Indian campaign / Reinhold Bichler -- Alexander and the palace of Memnon / Adam Łukaszewicz -- Cleomenes of Naucratis in pseudo-Aristotle's Oeconomica and the topoi of the ancient Egyptian propaganda / Ivan Ladynin -- P.OXY. 4808 and Historians / Robin Lane Fox -- Agatharchides of Cnidus and the idea of a peripatetic view of Alexander / Gościwit Malinowski -- In search of the many images of Alexander at Chaeronea. Historical and literary traditions in Plutarch's Corpus / Federicomaria Muccioli -- The miracles of water and oil in the historiography on Alexander / Sabine Müller -- The subtle and red line between reality and fiction : Alexander and his 'propaganda machine' / Giuseppe Squillace -- I Maccabees and the Alexander Romance / Krzysztof Nawotka -- Alexander and Caligula in the Jerusalem temple : a case of conflated traditions / Ory Amitay -- The Alexander historians in Byzantium / Corinne Jouanno.
This volume tries to tackle the most serious problem facing modern Alexander the Great studies: that of inadequate sources. Its principal interest is in surviving ancient continuous accounts (Diodorus, Curtius Rufus, Plutarch, Arrian, and Justin), which are at least three hundred years younger than Alexander and in many ways one-sided in their Greek bias, often promoting the view of Alexander within the narrow bounds of a Western conqueror. The papers in this volume deconstruct these accounts and search for sources used by their authors, principally in narrative of eye-witnesses and other authors of the first generation after Alexander, including his court historian Callisthenes and his companions Onesicritus, Aristobulus, and Ptolemy. They search for fragments of ancient literary works known from papyri and for shadowy accounts created on the Persian side like the "mercenaries' source". Some papers look into propaganda patterns of the age of Alexander and their connections with clichés of Egyptian literature. Some investigate a parallel tradition on the last will of Alexander, enshrined in "I Maccabees", and best known from the "Alexander Romance". Finally, papers in this volume examine post-classical rendition of Alexander: Jewish from the Talmud to Josippon and Byzantine, composed of separate textual traditions of various ancient authors, with Plutarch taking pride of place. Reihe Classica et Orientalia - Band 20
Includes bibliographical references (pages [211]-231) and indexes
In English; one contribution in French
Keywords: Alexander -- the Great -- 356 B.C.-323 B.C -- Sources; Alexander; Alexander - the Great - 356 B.C.-323 B.C; Alexander - the Great - 356 B.C.-323 B.C - Sources; Historiography; Sources; Historiographie; Historiography; Historiography; Konferenzschrift -- 2014 -- Warschau